Measurement of effectiveness spinning fiber machines using total productive maintenance method at textile manufacturing - Supriyadi, Edi; Nurdewanti, Rully (Universitas Mercu Buana, 2024)
PT XYZ is a textile industry manufacturing company whose main products are Polymer Chips, Pre-Oriented Yarn (POY), Draw Twister Yarn (DTY), Bi Shrankage Yarn (BSY), and Polyester Staple Fiber (PSF) which are marketed domestically and internationally. There are still high breakdown problems, which can hamper the production process and result in a decrease in production capacity. The purpose of this study was to measure the Performance Effectiveness of Fiber Spinning Machines using the Total Productive Maintenance (TPM) Method and to find the causes of the Six Big Losses that affect the Performance Effectiveness of Fiber Spinning Machines. The application of TPM in the manufacturing industry aims to extend machine life and maximize the effectiveness of machine performance. The results of measuring the Performance Effectiveness of Fiber Spinning Machines using the TPM Method obtained an Overall Equipment Effectiveness (OEE) value of 87.85% and the cause of Six Big Losses that affect the effectiveness of the performance of Fiber Spinning Machines is Equipment Failure Losses, the most dominant factor is the Human Factor, namely lack of control, lack of understanding of Standard Operational Procedure (SOP), lack of thoroughness when cleaning spinnerets.